Cross‐linked polymer electrolyte membrane based on a highly branched sulfonated polyimide with improved electrochemical properties for fuel cell applications. (9th September 2019) - Hu, Meishao; Zhang, Boping; Chen, Jiale; Xu, Muzi; Liu, Danqing; Wang, Lei
Summary: Sulfonated polyimides (SPIs) are extremely suitable as polymer electrolyte membranes (PEMs) for fuel cell applications, except for their poor water stability. Cross‐linking is a method that is commonly used to improve the weak hydrolytic stability of SPI membranes. However, this strategy significantly decreases the proton conductivity of the membrane, which leads to a lower fuel cell power density. In this work, a cross‐linked SPI membrane containing a highly branched polymer main chain was fabricated as a PEM. With a similar ion‐exchange capacity value, the cross‐linked membrane containing branched main chains showed an improved proton conductivity. Also, this membrane remained 92.3% of pristine weight after a hydrolytic stability test about 120 hours. In a single direct methanol fuel cell, the cross‐linked membrane containing a branched structure showed a higher power density (53.4 mW cm −2 ) than the common cross‐linked membrane (43.0 mW cm −2 ), indicating that branching is effective for improving the electrochemical properties of PEM‐based cross‐linked SPIs. Abstract : A cross‐linked SPI membrane (SPI‐BC) based on branched polymer main chain was fabricated as proton exchange membrane. By combing the merits of branching and cross‐linking, the SPI‐BC membrane exhibited great chemical stability. With a similar ion‐exchange capacity value, the SPI‐BC membrane showed an improved proton conductivity because of more free volume in polymer to accommodate water.